Quality Evaluation of Potato Starch Incorporated Chicken Meat Momos - Tanuja; Pathak, V.; Goswami, M. (Journal of Meat Science, 2018)
The chicken momos were prepared by replacing refined wheat flour with potato starch at three different levels i.e. P1 (4% potato starch), P2 (6% potato starch) and P3 (8% potato starch) and compared with control (C) with no added starch. The mean cooking yield, moisture content, carbohydrates and energy values increased significantly (P
Keywords: Chicken momos; Color estimation; Potato starch; Texture profile analysis